The Influence of Parenting Patterns and Socioeconomic Status on Self-Confidence and Motivation to Continue learning Among School dropouts - Redna Pratiwi; Sujarwo Sujarwo (Scidacplus, 2026)
This study aims to analyze the effects of parenting styles and socioeconomic status on self-confidence and motivation to continue education among school dropouts in Tanjung Steko Village. The research is motivated by persistently high dropout rates and low willingness among children to re-engage in formal education, which are closely associated with parental roles and family economic conditions. A quantitative causal approach was employed, involving 39 school dropouts selected through total sampling. Data were collected using questionnaires that had been tested for validity and reliability and were analyzed using multiple linear regression. The results indicate that parenting styles have a significant negative effect on self-confidence because of authoritarian or permissive styles rather than democratic ones. Whereas socioeconomic status has a significant positive effect. Simultaneously, both variables explain 39.1% of the variance in self-confidence and 32.8% of the variance in learning motivation. These findings emphasize that appropriate parenting practices and adequate family economic support play a crucial role in restoring school dropouts’ confidence and motivation to re-enter education.